2002
DOI: 10.1016/s0735-1097(02)02591-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of peripheral artery tonometry in the detection of treadmill exercise-induced myocardial ischemia

Abstract: Peripheral artery tonometry may be useful for improving the diagnosis of exercise-induced myocardial ischemia by both enhancing the sensitivity without impairing the specificity and increasing the percentage of definitive test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Chouraqui et al studied the accuracy of a similar technique in predicting exercise-induced myocardial ischemia. 24 PAT alone had a sensitivity of 58% and a specificity of 68%. When an ECG-PAT enhanced algorithm is used, the sensitivity and specificity improved to 64% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Chouraqui et al studied the accuracy of a similar technique in predicting exercise-induced myocardial ischemia. 24 PAT alone had a sensitivity of 58% and a specificity of 68%. When an ECG-PAT enhanced algorithm is used, the sensitivity and specificity improved to 64% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…CBF and tissue oxygenation measurements play an important role in evaluating various conditions such as vasospasm, ischemia, injury and recovery processes and cutaneous implant function [1,2]. The ability to monitor non-invasively changes in the skin microcirculation level leads to improvements both in diagnosis and treatment of patients [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that patients with coronary heart disease demonstrate changes in cutaneous microcirculation and a decrease in cutaneous blood mass [3,[8][9][10][11]. One of the suggested predictors of risk for cardiovascular disease is Endothelial Function which is based on sensitivity to long-acting nitrates and vasoactive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Chouraqui et al evaluated this concept further by adding PAT to standard 12-lead electrocardiography during exercise stress testing. 33 The rationale for this study was to use PAT to assess peripheral vascular function during exercise. The results of this study showed that PAT contributed to a 40% increase in diagnostic sensitivity over ECG alone with no loss of specificity.…”
Section: Initial Studies Utilizing Patmentioning
confidence: 99%